2010
DOI: 10.1007/s10499-010-9349-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of grouper Epinephelus coioides (Hamilton) larvae fed free-living nematode Panagrellus redivivus at first feeding

Abstract: The free-living nematode, Panagrellus redivivus, was tested as live food for grouper Epinephelus coioides larvae during the first feeding stage. A series of experiments were conducted to determine the acceptability of the free-living nematodes in grouper larvae at first feeding, the optimum nematode density and the response of the larvae to nutritionally enriched nematode. All experiments were conducted in 200-L conical tanks filled with 150-L filtered seawater and stocked at 15 larvae L -1 . Duration of feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…To support this theory, a study carried out by Focken et al (2006) revealed that the nematode Panagrellus redivivus was actively consumed by whiteleg shrimp larvae resulting in the nematode-fed shrimp reaching post-larval stage at a greater rate than the algae-only treatment. In another study, conducted by Reyes et al (2010), the authors demonstrated that up to 3 days post-hatch, orange spotted grouper (Epinephelus coioides) larvae actively fed on a diet of enriched P. redivivus; however, the authors concluded that without enrichment, the fatty acid profile contained in the nematodes is not sufficient to be considered a complete replacement to current commercial fishmeal and fish oil-based feeds. In short, nematodes within biofloc systems offer continuous access to a supplementary food source for the cultured organisms and can be actively preyed upon as and when required.…”
Section: Nematodesmentioning
confidence: 99%
“…To support this theory, a study carried out by Focken et al (2006) revealed that the nematode Panagrellus redivivus was actively consumed by whiteleg shrimp larvae resulting in the nematode-fed shrimp reaching post-larval stage at a greater rate than the algae-only treatment. In another study, conducted by Reyes et al (2010), the authors demonstrated that up to 3 days post-hatch, orange spotted grouper (Epinephelus coioides) larvae actively fed on a diet of enriched P. redivivus; however, the authors concluded that without enrichment, the fatty acid profile contained in the nematodes is not sufficient to be considered a complete replacement to current commercial fishmeal and fish oil-based feeds. In short, nematodes within biofloc systems offer continuous access to a supplementary food source for the cultured organisms and can be actively preyed upon as and when required.…”
Section: Nematodesmentioning
confidence: 99%
“…To reduce dependence on brine shrimp, research has focused on using free‐living and non‐parasitic microbivorous nematodes (Brüggemann, ). Previously, the nematode Panagrellus redivivus was used as live prey to replace Artemia for marine (Reyes, Duray, Santiago & Ricci, ) and freshwater fish (Sautter, Kaiser, Focken & Becker, ; Schlechtriem, Ricci, Focken & Becker, ), and crustaceans (Kumlu, ; Kumlu, Fletcher & Fisher, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important aspect of producing annelids and nematodes is the ease of nutritional composition enhancement. Inclusion of fish meal and oil results in culture mediums results in high quality nutritional quality both for nematodes and annelids (Delbare and Dhert, 1996;Ricci, 2001;Santiago et al, 2003;Reyes et al, 2011;Schlechtriem et al, 2004;Kumlu et al, 1998;Santiago et al, 2004;Ercan et al, 2018).…”
mentioning
confidence: 99%